A Review of Selected Genes with Known Effects on Performance and Health of Cattle - Casas, Eduardo; Kehrli, Marcus E. (Frontiers in Veterinary Science, 2016)
There are genetic conditions that influence production in dairy and beef cattle. The objective of this review was to describe relevant genetic conditions that have been associated with productivity and health in cattle. Genes or genomic regions that have been identified as a candidate for the condition will be included, and the genetic basis of the condition will be defined. Genes and genetic conditions included in this review are bovine leukocyte adhesion deficiency, deficiency of the uridine monophosphate synthase, bovine chronic interstitial nephritis, horn development, myostatin, complex vertebral malformation, leptin, osteopetrosis, apoptosis peptide activating factor 1, chondrodysplastic dwarfism, caseins, calpastatin, umbilical hernia, lactoglobulin, citrullinemia, cholesterol deficiency, prions, thyroglobulin, diacylglycerol acyltransferase, syndactyly, maple syrup urine disease, slick hair, Factor XI deficiency, and μ-Calpain. This review is not meant to be comprehensive, and relevant information is provided to ascertain genetic markers associated with the conditions.